ROLE OF THE INTERNET AS AN ALTERNATIVE IN THE WEB MEDIA PROMOTIONS AT PERTAMINA UPPDN - IV SEMARANG - Irman Harviannur Saleh; Susi Wagiyati, SKom, MM Susi Wagiyati, SKom, MM (Jurnal Sistem Informasi, 2000)
The speed in obtaining information and communications become one tip to seizeopportunities. Pertamina as one of the tricks to seize opportunities. Pertamina as oneBMN company engaged in exploitation of natural resources, namely oil and naturalgas. Pertamina has a wide working area, covering the whole of Indonesia. To facecompetition in the free market will, needed a big campaign to introduce the productand provide information needed by customers or investors. Web is one solution indealing with these problems Using other than traditional media. By using the web onthe internet will reach a wider area without borders. Its use can reach other countriesand continents where else, also no time limit. So pertamina web will be accessible bycustomers and investors at any time 24 (twenty four) hour, with a cheaper cost. Witha good design will certainly attract Internet users to access or visit the web pertaminato obtain the required information.